2015
DOI: 10.1038/srep14172
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity promotes osteoclast activity in medaka fish reared at the international space station

Abstract: The bone mineral density (BMD) of astronauts decreases specifically in the weight-bearing sites during spaceflight. It seems that osteoclasts would be affected by a change in gravity; however, the molecular mechanism involved remains unclear. Here, we show that the mineral density of the pharyngeal bone and teeth region of TRAP-GFP/Osterix-DsRed double transgenic medaka fish was decreased and that osteoclasts were activated when the fish were reared for 56 days at the international space station. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…In our results, expressions of these genes were altered under microgravity, which thus suggests that NO-GR signaling is related to the “microgravitational stress”. Taken together, available data indicate that the GR is the main molecule involved in the effect of microgravity on cells, consistent with our observations of activation of GRs in medaka fish reared long-term in the ISS21. Finally, to clarify the GR action under microgravity, further analyses are required.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our results, expressions of these genes were altered under microgravity, which thus suggests that NO-GR signaling is related to the “microgravitational stress”. Taken together, available data indicate that the GR is the main molecule involved in the effect of microgravity on cells, consistent with our observations of activation of GRs in medaka fish reared long-term in the ISS21. Finally, to clarify the GR action under microgravity, further analyses are required.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that there are many osteoblasts and osteoclasts in pharyngeal bones21, and osteoblasts are important for osteoclastogenesis in these bones15. To study the co-localization of osteoblasts and osteoclasts, we observed osterix -DsRed/ TRAP -GFP merged images (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations